Englis - Fahmi Arief Rahman; Vinda Nur Septya Wulan; Sinar Suryawati; Erick Yuhardi; Slamet Supriyadi (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
Bojonegoro Regency is one of the rice-producing areas but is prone to drought, as occurred in 2019-2020. Remote sensing is a solution for mitigation and adaptation to reduce the impact of drought. The study aimed to determine the spatial and temporal distribution of drought in Bojonegoro Regency in 2023. This study utilizes GEE, a cloud-based computing platform used to analyze land cover parameters, rainfall, LST, NDVI, NDWI, and NDDI. The results showed that rainfall in Bojonegoro varies, with the highest levels occurring in January-March and the lowest levels, marking the peak of the drought, in July-September. The LST category is very high and evenly distributed across the entire region from July to December. The average NDVI values obtained from July to December fall into the moderate category, but in some locations, they fall into the low vegetation category. NDWI classification falls into the moderate category from July to December. Meanwhile, the peak of drought (NDDI) occurs from July to December. This study is useful for supporting drought mitigation and adaptation strategies for farmers in Bojonegoro Regency based on spatial and temporal patterns.